2002
DOI: 10.1007/bf03166126
|View full text |Cite
|
Sign up to set email alerts
|

Application of time-variable feedback to the input amplifier of pulse magnetic resonance spectrometers: Experimental studies

Abstract: Experimental research on the improvement of the sensitivity and time resolution of pulsed magnetic resonance spectrometers is discussed. It is shown that application of a time-variable feedback of a signal to the input of the receiver amplifier can decouple the "fixed" relationship between the quality factor Q and the ringdown time of the resonance system. Experiments were performed with low-frequency, radio-frequency and microwave pulse-type magnetic resonance receivers. Modifications of an S/C-band electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…A proper model should not be too complex and at the same time should enable one to perform the required generalized analysis. Equivalent diagrams with lumped elements have been established as a good choice [10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29]. In the present approach the resonator ~ and coupling structure are modelled asa set of lumped elements: inductors, capacitors and resistors.…”
Section: Equivalent-diagram Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A proper model should not be too complex and at the same time should enable one to perform the required generalized analysis. Equivalent diagrams with lumped elements have been established as a good choice [10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29]. In the present approach the resonator ~ and coupling structure are modelled asa set of lumped elements: inductors, capacitors and resistors.…”
Section: Equivalent-diagram Analysismentioning
confidence: 99%
“…With the pulse spectrometer systems it could be of advantage to change the input receiver bandwidth with submicrosecond time resolution to provide a shorter receiver "dead time". Recently it was suggested to use "time-variable" feedback in the input amplifier to conduct such a fast bandwidth change [19][20][21]. The experiments performed have shown that receivers with time-variable feedback could be very promising for the pulse spectrometers, but some effects were hard to comprehend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation